2019
DOI: 10.7717/peerj.6365
|View full text |Cite
|
Sign up to set email alerts
|

Exploring wearable sensors as an alternative to marker-based motion capture in the pitching delivery

Abstract: BackgroundImprovements in data processing, increased understanding of the biomechanical background behind kinetics and kinematics, and technological advancements in inertial measurement unit (IMU) sensors have enabled high precision in the measurement of joint angles and acceleration on human subjects. This has resulted in new devices that reportedly measure joint angles, arm speed, and stresses to the pitching arms of baseball players. This study seeks to validate one such sensor, the MotusBASEBALL unit, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 24 publications
(24 reference statements)
1
38
0
Order By: Relevance
“…The application of the inertial sensors to the professional sports has reached a large number of throws in this study and showed that increase of elbow varus torque associated with arm mechanics. Furthermore, Boddy and et al recently examined the validation of the inertial sensor to a biomechanical analysis of baseball pitching (14). They have demonstrated the differences between elbow mounted "Motus BASEBALL sensor" for the joint angle measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of the inertial sensors to the professional sports has reached a large number of throws in this study and showed that increase of elbow varus torque associated with arm mechanics. Furthermore, Boddy and et al recently examined the validation of the inertial sensor to a biomechanical analysis of baseball pitching (14). They have demonstrated the differences between elbow mounted "Motus BASEBALL sensor" for the joint angle measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accelerometer and IMUbased wearable technology emerged to use for overarm throwing performance assessment. Previous studies have revealed that wearable sensor's motion capture abilities, for instance, quantified the throwing activity (12), kinematic analysis of overarm throwing and comparison with lab-based systems (13,14). However, the accelerometer-based throwing velocity evaluation has only been established in one study with a low sampling frequency (250 Hz) (15).…”
Section: Introductionmentioning
confidence: 99%
“…In the present research, IMU signals were compared to those of an OMC system (Optitrack, NaturalPoint Inc., Oregon, USA) existing of eight cameras (model Prime 41) recording at a speed of 128 Hz. This OMC system has been used in similar studies 10,23 and considered as accurate as other well-established motion capture systems. 24 A cluster of five reflective (passive) markers of 12.7 mm diameter were fixed to the plastic rigid body, constituting the OMC gyroscope (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, their relative affordability respect to optical-tracking systems, the faster and simpler setups, and the advantage of not being confined to a laboratory setting, make them ideal tools for assessing ROM in the clinical practice (Ahmad et al, 2013). There are several reviews which explore the usage of these instruments for a variety of health purposes, yielding interesting research in biomechanics, such as the classification of age-related kinematic impairment (Greene et al, 2015;Roldán-Jiménez & Cuesta-Vargas, 2016), body mobility assessment (Iwasaki & Hirotomi, 2015), gait analysis and development of athletes' performance (Camomilla et al, 2018) and sports (Boddy et al, 2019;Wells et al, 2019).…”
Section: Introductionmentioning
confidence: 99%